2015
DOI: 10.1111/cas.12645
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced antitumor effect of anti‐tissue factor antibody‐conjugated epirubicin‐incorporating micelles in xenograft models

Abstract: For the creation of a successful antibody–drug conjugate (ADC), both scientific and clinical evidence has indicated that highly toxic anticancer agents (ACA) should be conjugated to a monoclonal antibody (mAb) to administer a reasonable amount of ADC to patients without compromising the affinity of the mAb. For ordinary ACA, the conjugation of a mAb to ACA-loaded micellar nanoparticles is clinically applicable. Tissue factor (TF) is often overexpressed in various cancer cells and tumor vascular endothelium. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 42 publications
2
28
0
Order By: Relevance
“…In the present study, anti‐TF1859‐NC‐6300 showed superior antitumor activity to NC‐6300 in the TF‐high expressing human pancreatic cancer model. This is similar to our previous report concerning anti‐TF1849‐NC‐6300 . Anti‐TF1849‐NC‐6300 was distributed throughout all of the tumor tissues and was efficiently internalized into tumor cells; it showed potent antitumor activity in TF‐high expressing cancer cells, indicating that the conjugation of anti‐TF mAb to micelles offered that advantage.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, anti‐TF1859‐NC‐6300 showed superior antitumor activity to NC‐6300 in the TF‐high expressing human pancreatic cancer model. This is similar to our previous report concerning anti‐TF1849‐NC‐6300 . Anti‐TF1849‐NC‐6300 was distributed throughout all of the tumor tissues and was efficiently internalized into tumor cells; it showed potent antitumor activity in TF‐high expressing cancer cells, indicating that the conjugation of anti‐TF mAb to micelles offered that advantage.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, overexpression of TF on tumor cells is closely related to poor patient prognosis in various cancers . We previously developed an anti‐TF antibody (clone 1849) conjugated with NC‐6300 (anti‐TF1849‐NC‐6300) and showed that it had superior antitumor activity when compared with NC‐6300 alone …”
mentioning
confidence: 99%
“…As a result, EPI has less side effects compared with DOX at doses producing equivalent antitumor effects [35]. EPI therefore has been nanosized to various formulations such as micelles [36], liposomes [37], nanoparticles [38,39], and, most interesting for us, water-soluble conjugates to improve its therapeutic index. In general, polymer-EPI conjugates were produced via polymeranalogous reaction in which EPI is attached to polymer through active ester [27] or in the presence of coupling agents [25,28].…”
Section: Resultsmentioning
confidence: 99%
“…These immunomicelles were conjugated with antibodies targeting osteopontin, epidermal growth factor receptor, human epidermal growth factor receptor‐2, and others. Recently, we reported immunomicelles conjugated with anti‐tissue factor (TF) antibody fragments . Tissue factor is known as a primary initiator of blood coagulation, and plays an important role in tumor proliferation, invasion, and metastasis .…”
Section: Design Of Polymeric Micelles For Targeting Intractable Cancersmentioning
confidence: 99%
“…Importantly, these properties, which might critically affect the performance as a drug carrier, can be optimized by fine‐tuning chemical structures and compositions of the micelle‐forming block copolymers . In addition, installation of functional molecules such as environment‐responsive cleavable linkages and targetable ligands on the block copolymers allows construction of polymeric micelles with smart functionalities . Owing to the above‐mentioned prominent advantages beyond other drug vehicles, several micellar formulations of anticancer drugs are currently under evaluation in preclinical and clinical studies .…”
mentioning
confidence: 94%